2016
DOI: 10.1103/physrevc.94.025201
|View full text |Cite
|
Sign up to set email alerts
|

Λpinteraction studied via femtoscopy inp+Nbreactions ats

Abstract: We report on the first measurement of pΛ and pp correlations via the femtoscopy method in p+Nb reactions at √ sNN = 3.18 GeV, studied with the High Acceptance Di-Electron Spectrometer (HADES). By comparing the experimental correlation function to model calculations, a source size for pp pairs of r0,pp = 2.02 ± 0.01(stat) +0.11 −0.12 (sys) fm and a slightly smaller value for pΛ of r0,Λp = 1.62 ± 0.02(stat) +0.19 −0.08 (sys) fm is extracted. Using the geometrical extent of the particle emitting region, deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The hyperon-nucleon (Y N ) interaction can be tested experimentally via scattering experiments employing secondary hyperon beams [196][197][198], impinging on hydrogen targets, or by means of the measurement of the correlation in the momentum space for hyperon-proton (Y p) pairs produced at colliders exploiting the femtoscopy technique [19,38,39,199].…”
Section: Experimental Searchesmentioning
confidence: 99%
“…The hyperon-nucleon (Y N ) interaction can be tested experimentally via scattering experiments employing secondary hyperon beams [196][197][198], impinging on hydrogen targets, or by means of the measurement of the correlation in the momentum space for hyperon-proton (Y p) pairs produced at colliders exploiting the femtoscopy technique [19,38,39,199].…”
Section: Experimental Searchesmentioning
confidence: 99%
“…In particular two different transport models are used to model the source: UrQMD [74] for simulating p-Nb reactions at √ s NN = 3.18 GeV and EPOS [18] for simulating pp reactions at √ s = 7 TeV. The p-Nb system is expected to have a Gaussian source of around 2 fm [75], while the pp system produces a much smaller source, comparable to a Gaussian source of below 1 fm (see Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order to apply the CATS framework to experimental data we present, in Fig. 12, the result for the p-p correlation function obtained in p-Nb collisions at √ s NN = 3.18 GeV [75]. We evaluated C(k) in CATS using the Av 18 potential with s-and p-waves included and performed a fit to the data by multiplying C(k) with a normalization constant N. The source is assumed to be Gaussian and the source size is a free fit parameter.…”
Section: It Is Clear That For Sources ≥ 2 Fm the Correlation Function Ismentioning
confidence: 99%
“…In particular, it was demonstrated that the momentum correlations between a pair of hadrons produced in heavy-ion collisions not only depend on quantum statistical effects and the space-time structure of the emitting source [29][30][31][32][33][34][35][36][37] but also are sensitive to the final-state interactions of the emitted hadron pair [38][39][40][41][42]. Because of the abundant hyperons produced in relativistic heavy-ion collisions and the excellent capabilities of detectors to identify particles and measure their momenta, the measurements of momentum correlation functions have become invaluable to reveal the precise dynamics of the strong interactions between a pair of hadrons, including meson-meson [43][44][45][46][47], meson-baryon [48][49][50], and (anti)baryon-(anti)baryon [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. The measurements of momentum correlation functions have also triggered a large amount of related theoretical studies [66][67][68][69][70][71...…”
Section: Introductionmentioning
confidence: 99%